Risiko Infeksi Kecacingan pada Penambang Intan Tradisional di Kecamatan Cempaka Kota Banjarbaru - Erfan Roebiakto; Yohanes Joko Supriyadi (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2016)
Abstract: The Potential danger from mining activities is a worm infection. worm infection is often found in the community and are often considered harmless. This condition if left unchecked will lead to malnutrition, decreased endurance and work productivity. The aim of research to determine the risk factors and the incidence of worm infection on a traditional diamond miners in the district Cempaka Banjarbaru. This research is an analytic study with cross sectional design with a sample size of 60 people. The variables studied were the risk factors and the incidence of worm infection. The results of the study of risk factors normal nutritional status of respondents (46.7%), lack of knowledge level (63.3%); using Rescue Tool in work (63.3%); Good personal hygiene (51.7%), bowel habits are not eligible (60.0%) and worm infection (33.3%). The statistical test result with Che-Square test (X2), there was a significant relationship between risk factors and the incidence of worm disease in miners (p ˂ 0.05). Expected workers use personal protective equipment, health checked regularly and get a clean and healthy living behavior.